A simplified semi-empirical model for multifrequency seafloor backscattering angular response (ESAB) - Fonseca, Luciano; Lurton, Xavier; Fezzani, Ridha; Roche, Marc (Frontiers in Remote Sensing, 2025)
A new approach to seafloor acoustic backscatter prediction and inversion is presented here and applied to an experimental dataset. Based on a frequency-dependent semi-empirical geometrical-physical description, the Extended Seabed Acoustic Backscatter (ESAB) model addresses the seabed backscatter angular response over a wide frequency range, a key issue today in seafloor-mapping operations using multibeam echosounders. Starting from classical backscatter models, ESAB considers three main physical parameters corresponding to acoustical properties prevalent in seabed scattering phenomena: acoustical impedance, roughness facet-slope variance and sediment-volume scattering index. Classical theories are applied to describe the main backscatter components, for interface roughness (facets and Bragg) and sediment volume, modified to explicitly account for frequency. A special effort was applied for introducing an objective frequency dependence in the classical facets method using developments involving various aspects of the roughness properties, building on previous classical works. The interface and volume components are completed by geoacoustical relationships constraining the range of input parameters, as well as by connection terms that ensure numerical stability. The model proved effective across a frequency range corresponding at least to our available angle/frequency field data. Beyond its wide applicability domain, a key advantage of ESAB is its ability to maintain mathematical simplicity and numerical versatility, akin to its predecessor GSAB while providing a direct physical interpretation of parameters, requiring limited assumptions about the sediment physical nature and accounting for frequency dependence. The model effectiveness is demonstrated by the analysis of a comprehensive dataset from the Concarneau Bay (France), providing backscatter measurements acquired by a calibrated EK80 split-beam echosounder across wide incidence angle (0°–70°) and frequency (35–440 kHz) ranges for seven distinct geological facies. The inversion was performed through a simulated annealing algorithm, providing the three main seafloor parameters together with intermediate results. It provided stable and consistent results over the whole frequency range, confirming ESAB’s capability to accurately fit different angular and frequency response patterns while providing quantified and physically meaningful insights into seafloor characteristics. This dual capability of numerical versatility and physical interpretability makes ESAB particularly valuable for seafloor characterization applications involving multifrequency multibeam echosounders for backscatter angular response measurements.